STUDI ADSORPSI DAN DESORPSI REDUKTIF PADA PEMBENTUKAN NANOPARTIKEL EMAS DARI PRINTED CIRCUIT BOARDS - ALFANAAR, ROKIY ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Gold nanoparticles have been synthesis from waste printed circuit boards (PCB) through process of adsorption using Mg/Al hydrotalcite and reductive desorption using sodium citrate and glutamatic acid. The research was first initiated by reducing the content of non-precious metals from PCB using double oxidation-acid leaching method with a mixed solution of H2O2 30%-H2SO4 3 M at a volume ratio of 3: 1 and the time of leaching 3 days. The Cu metal released after leaching as 25449 mg/L (254.49 mg Cu/g PCB). The second process was microwave assisted-aqua regia leaching for Au and it was able to leach Au 137 mg/L (1.37 mg Au/g PCB). The leached Au was adsorbed to Mg / Al hydrotalcite and followed by desorption using 0.5 M NaOH. The desorbed Au was then reduced to produce gold nanoparticles by using sodium citrate and glutamic acid as capping agent. Maximum surface plama resonance of gold nanoparticles was obtained at concentrations of sodium citrate 60 mM and glutamate 80 mM.